The equivalent Cauchy sequences in partial metric spaces. - Hoxha, Elida (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper we prove some conditions for equivalent Cauchy sequences in partial metric spaces. These conditions are necessary and sufficient for 0-equivalent 0-Cauchy sequences in partial metric spaces. Some examples are given to illustrate the observed results.